Incidence, Risk Factors, and Effect on Allograft Survival of Glomerulonephritis Post-transplantation in a United Kingdom Population: Cohort Study - Aguiar, Rute; Bourmpaki, Elli; Bunce, Catey; Coker, Bola; Delaney, Florence; de Jongh, Leonardo; Oliveira, Giovani; Weir, Alistair; Higgins, Finola; Spiridou, Anastasia; Hasan, Syed; Smith, Jonathan; et al. (Frontiers in Nephrology, 2022)
Background: Post-transplant glomerulonephritis (PTGN) has been associated with inferior long-term allograft survival and its incidence varies widely in the literature. Methods: Cohort study of 7623 patients transplanted between 2005 and 2016 at four major transplant UK centres. Diagnosis of GN in the allograft was extracted from histology reports aided by use of text-mining software. Incidence of the four commonest GN post-transplantation was calculated and risk factors for disease and allograft outcomes were analysed. Results: 214 patients (2.8%) presented PTGN. IgA Nephropathy (IgAN), Focal segmental glomerulosclerosis (FSGS), Membranous nephropathy (MN) and Membranoproliferative/Mesangiocapillary GN (MPGN/MCGN) were the four commonest forms of post-transplant GN. Living donation, HLA DR match, mixed race and other ethnic minority groups were associated with an increased risk of developing a PTGN. Patients with PTGN showed a similar allograft survival than those without in the first 8 years post-transplantation, but results suggest they do less well after that timepoint. IgAN was associated with the best allograft survival and FSGS with the worst allograft survival. Conclusions: PTGN has an important impact on long-term allograft survival. Significant challenges can be encountered when attempting to analyse large scale data involving unstructured or complex data points and use of computational analysis can assist.